Peparation and Characterization of Solid Dispersion of Tinidazole with Benzoic Acid and Tartaric Acid (2016)
ABSTRACT: Two solid dispersions (SDs) were prepared in order to increase the dissolution rate of tinidazole (TND) by applying the method of grinding and moisturizing with drops of ethanol, using tartaric acid (TTA) and benzoic acid (BZA) as carrier agents. These carrier agents showed complete miscibility with TND, according to the DSC results. The two SDs were characterized and compared with pure TND through XRPD, DSC, FT-IR, particle size, water saturation solubility, equivalent specific surface, wettability and intrinsic dissolution rate tests. All samples were evaluated in the same particle range, and it was found that the increase in the dissolution of the two SDs in comparison to the pure drug was not a result of the reduced particle size but of the partial amorphization of the TND. The carrier-drug ratio makes the TND dosage in these two dispersions a promising alternative for the tablet form.